2018
DOI: 10.1021/acsami.8b07980
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Flexibility and Microwave Absorption Properties of HfC/SiC Nanofiber Mats

Abstract: Hafnium carbide (HfC) phase, with a high melting point, excellent strength, and high electrical conductivity, could be a suitable addition to enhance the microwave absorption properties of one-dimensional silicon carbide (SiC) nanomaterials without sacrificing its high-temperature thermal stability. In the present work, HfC/SiC hybrid nanofiber mats with different HfC loading contents are fabricated by electrospinning and high-temperature pyrolysis. HfC hybrids with sizes of 5-10 nm are embedded in the SiC nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 56 publications
0
68
0
1
Order By: Relevance
“…To fabricate large‐scale, lightweight, and broadband MA materials, conductive carbon composites with special structure have been extensively studied, such as MWCNTs, carbon fiber, cotton cloth, and carbon cloth (CC) . Ji and co‐workers synthesized cotton/zeolitic imidazolate framework (ZIF) and carbon‐cotton/Co@nanoporous carbon absorber from biomass cotton .…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate large‐scale, lightweight, and broadband MA materials, conductive carbon composites with special structure have been extensively studied, such as MWCNTs, carbon fiber, cotton cloth, and carbon cloth (CC) . Ji and co‐workers synthesized cotton/zeolitic imidazolate framework (ZIF) and carbon‐cotton/Co@nanoporous carbon absorber from biomass cotton .…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 3a S4 (Supplementary Materials); with decreased B content, the B atomic percent showed an upward trend, the N atomic percent first decreased and then increased, the C atomic percent showed a trend of increasing and then decreasing; consistent with the variation of B-C and B-N groups in the B,N-CNTs. The reflection loss (RL) of carbon nanomaterial can be used to characterize its MA property in the transmission-line theory, and the calculation formulas are shown in Equations (1) and (2) [38]:…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of MA performance of B,N-CNT-2 was mainly caused that the appropriate addition of B element led to more defects on the surface of B,N-CNT and thus increased the interfacial polarization of the absorbent. Compared with the RL curve of B,N-CNT-2, it was clearly shown that the lowest RL of B,N-CNT-3 was increased to −16.5 dB at 18 GHz, and the effective absorption bandwidth was only 1 GHz with a thickness of 5 mm The reflection loss (RL) of carbon nanomaterial can be used to characterize its MA property in the transmission-line theory, and the calculation formulas are shown in Equations ( 1) and (2) [38]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the fabrication of an efficient EMA material has evoked great attention, which means the material not only have strong adsorption and broad bandwidth but also light and thin at the same time. [ 7–9 ] To date, researchers are interested in fabricating novel EMA materials, including carbon, [ 10 ] silicon carbide, [ 11 ] zinc oxide, [ 12 ] MXene, [ 13 ] metal–organic framework (MOF), [ 14–16 ] etc.…”
Section: Introductionmentioning
confidence: 99%